Bi-allelic variants in NRDC cause a neurodevelopmental disorder characterized by neonatal lethality, microcephaly, and brain abnormalities. - Pehlivan, D.; Sandoval, A.; Maroofian, R.; Lecoquierre, F.; Al Shamsi, A.M.; Lee, G.S.; Yesilbas, O.; Taylor, P.; McDougal, M.B.; Bahrambeigi, V.; Aryani, O.; Ramirez, J.F.; et al. (American Journal of Human Genetics, 2026)
Nardilysin (NRDC) plays a role in multiple cellular functions in diverse cellular compartments, including ectodomain shedding in the plasma membrane, as well as chaperoning a key Krebs cycle enzyme in mitochondria. We had previously reported limited clinical information from two individuals with homozygous frameshift variants in NRDC. With inclusion of previously published individuals, here we report 14 individuals (10 females, four males) from nine unrelated families carrying homozygous NRDC pathogenic variants. Common clinical features include severe to profound developmental delay/intellectual disability (12/12), microcephaly (13/13), prematurity (5/13), lethality in the first 3 years of life (9/14), seizures (7/11), joint contractures (4/8), eye/visual abnormalities (5/7), and abnormal brain imaging studies ranging from diffuse atrophy to lissencephaly (8/11). The identified variants include two splice, three frameshift, and three missense variants. RT-PCR from affected individual fibroblasts and a minigene assay in HEK293T cells demonstrate that the splice variants led to exon skipping of NRDC. To further investigate the pathogenicity of the variants in vivo, we used the Drosophila Nrdc (dNrdc) mutant model. dNrdc null mutants caused developmental lethality, which is fully rescued by wild-type human NRDC. Studies in the Drosophila dNrdc mutant models showed that both splice variants and frameshift variants cause severe loss of function, leading to lethality, whereas missense variants cause partial lethality and short lifespan, consistent with less severe phenotype. Our data establish that homozygous variants in NRDC are pathogenic, leading to highly lethal and severe neurodevelopmental disorder in humans.